Valorisation of shell waste of invasive crayfish from Danube River (Faxonius limosus): Protein extraction and characterization - Hromiš Nevena M.; Popović Senka Z.; Šuput Danijela Z.; Pantić Jovana R.; Rakita Slađana M.; Tomičić Zorica M.; Čabarkapa Ivana S. (Food and Feed Research)
In order to deal with invasive crayfish (Faxonius limosus) impact on the native crayfish, as well as fish biodiversity in the Danube River, a possible solution would be to find and adopt mechanisms for its utilization for novel valuable product production. Apart from utilizing edible parts for novel food products, the shell waste can also be considered a source of valuable compounds. The complex structure of the shell mainly consists of three basic compounds: chitin, protein and minerals-mainly calcium carbonate. In this study, shell waste proteins were extracted using three extraction methods. The first method involved using naturally present enzymes (proteases and lipases) in crayfish wastes to recover proteins through an autolysis process. To accelerate the process, UV radiation was used. The remaining two extraction methods were alkaline extraction of proteins, wherein one method alkaline extraction was applied directly to the shell waste, and the other method, alkaline extraction followed an acidic demineralization step of the shell waste. The obtained protein concentrates were analysed for yield, crude protein content, DPPH radical scavenging ability, amino acid content, and structure. The results have shown that a similar percentage of protein content was obtained by all three methods: 67.20-68.03 %, but the extraction yield was considerably different. Alkaline deproteinization with or without the step of demineralization resulted in a 9.20-10.98 % yield, while UV radiation accelerated autolysis resulted in only a 3.41 % yield. Although protein extraction without using exogenous enzymes or chemicals is a very interesting approach, a drawback of this approach is the low process yield. FTIR spectroscopy revealed a secondary structure that was similar in all three concentrates, according to peak deconvolution, with the autolytic concentrate differing to a lesser extent, showing a slightly higher share of b-sheet structures. The DPPH assay revealed high antioxidant activity of the concentrates (72.00-88.06 %), probably originating from active peptides derived from proteins and residual carotenoids, mainly astaxanthin.